Plant growth promoting and biocontrol activities of cold-tolerant Pseudomonas fluorescens isolates against root rot in pea - and J. KUMAR*, YOGESH K. NEGI, S.K. GARG (Indian Phytopathology, 2008)
Several reports in the past have shown incongruent performance of Pseudomonas fluorescens (Pf) strains with respect to plant growth promotion and biocontrol activities when tested under controlled and field conditions. However, we found consistent performance of the native Pfs and their combinations from Uttarankhand hills in garden pea. A set of five isolates, possessing good biocontrol activity against Fusarium solani f.sp. pisi and plant growth promotion activities, was tested for both the activities in garden pea under poly house and field conditions. Among these, isolates Pf-551 and Pf-572 individually and in combination with Pf-173 and Pf-547 were found effective with respect to plant growth promotion and biocontrol activities. Combinations of Pf-173+ Pf-193 + Pf-551+ Pf-572 and Pf-173+ Pf-193+ Pf-547+ Pf-551+ Pf-572 were best in increasing yield under field conditions. Significant reduction in plant mortality under polyhouse (63.3-100%) and field (20-100%) was recorded under different treatments, which indicated that the test isolates were good biocontrol agents against Fusarium solani f.sp. pisi. Enhanced plant growth parameters in pea suggested that the isolates were good PGPRs as well. Consistent performance of these isolates under field conditions could be because the isolates were native to the environment where they were used.